MENEROPONG MASA DEPAN KOMUNITAS ASEAN 2015: Studi Prediksi atas Komunitas ASEAN di Asia Tenggara - Sugiarto Pramono (Universitas Wahid Hasyim Semarang, 2010)
AbstractIn this paper—through four barometers—writer predicts future ASEAN Community 2015: (1) geography, which is shaped continents or islands, (2) etnicity, homogeneous or hiterogen, (3) the intensity of the war in the past, how often and big? and (4) how much of the political will of key policy makers to create a regional community?. At the end of the article concluded that the ASEAN community 2015, apparently through steep winding road, if not fail.Key words: community, regionality, integration